BUSINESS ENVIRONMENT, INNOVATION CAPABILITY AND BUSINESS PERFORMANCE: EMPIRICAL STUDY OF JAKARTA’S FLOUR BASED FOOD SMEs - V. Rachmadi Parmono; Y. Eko Widodo (Journal of Management and Business, 2009)
This study is concerned on the relationship between innovation capability and business performance in small and medium enterprises context. The existing studies generally have analyzed the issues pertaining of innovation capability in large business or knowledge intensive firm context. By researching of the innovation capability of small and medium enterprises (SME’s), it will review innovation capability in a broader and novel context. The SME’s operate in a competitive environment and are not very advanced technologically. This research proposes statistical hypotheses to study these based on data samples. By employing path analysis, This research test the relationship between innovation categories and business performance. The result of our study show that government regulation directly affects to innovation capability, product and process innovation capability directly affect business performance in SME’s. Finally, managerial implication will be discussed.